Małgorzata Hołda, Paul Ricoeur’s Concept of Subjectivity and the Postmodern Claim of the Death of the Subject, Ignatianum University Press, Cracow 2018 (rev.) - Graves, Adam (Studia Philosophiae Christianae, 2019)
Holda’s defense of Ricoeur’s so-called philosophy of subjectivity as a viable and coherent alternative to the postmodern critique of the subject is itself valuable addition to our understanding of the topic, as well as to our understanding of the place of Ricoeur within late twentieth-century French philosophy.